Unintended and undesired consequences: The impact of OECD Pillar I and II proposals on small open economies - Matthias Bauer (European Centre for International Political Economy (ECIPE), 2020)
Corporate tax laws vary significantly between different jurisdictions. Over the past four decades, governments globally competed for business activity by lowering statutory and effective corporate tax rates. Many governments provide special tax incentives for businesses to invest and expand employment. Special economic zones often grant full corporate tax exemptions to stimulate commercial development. Corporate income tax incentives for research and development activities are common across countries' corporate tax codes reflecting governments' desire to stimulate innovation and business development. While corporate tax competition is common government practice in the world economy, the OECD currently aims to curb international corporate tax competition. The OECD's corporate tax reform proposals officially aim to address "corporate tax avoidance" and "unfairness in taxation". The policy debate is driven by some governments' motivation to increase revenues from taxes on corporate income. Economic impact assessments of the OECD's current Pillar I and II proposals are still scarce. Individual governments have so far failed to conduct impact assessments or are hesitant to make their assessments available to the general public. The OECD's secretariat expects additional tax revenues of 100bn USD annually, which are said to be evenly distributed among the 137 countries comprising the Inclusive Framework. The narrow focus on changes in governments' revenues and the static nature of the OECD's analysis is in various respects misleading. This paper highlights that the proposed reforms would shift taxing powers (tax sovereignty) and economic activity away from small open economies to the world's largest countries, of which most (currently) apply very high statutory corporate tax rates. The implementation of Pillar I and II proposals would pave the way for a global tax redistribution framework transferring financial funds away from governments that embrace free international trade and investment to the many of the world's worst-performing governments with respect to economic openness, acceptance of the rule of law, corruption, state interventionism, and the recognition of basic human rights (e.g. Argentina, Brazil, China, India, Indonesia and Russia). Conversely, the OECD's proposed corporate tax reforms would punish the world's best performing economies with regard to economic freedoms, trade and investment openness and the rule of law (e.g. Estonia, the Czech Republic, Ireland, the Netherlands, Slovakia, Slovenia, Switzerland, including small city and island states, such as Hong Kong, Luxembourg and Singapore).
Keywords: 330; Internationale Unternehmensbesteuerung; Wettbewerbsvorteil; OECD-Staaten